Developing a Shared Decision-Making Model for Diabetic Patients: A Qualitative Study: - Vaskouei Eshkevarei, khorshid; Hajinabi, Kamran; Riahi, Leila; Maleki, Mohammadreza (Galen Medical Journal, 2021)
Background: Patient participation in healthcare leads to increased satisfaction and trust, reduction of anxiety, and a better understanding of patients’ needs. The components of shared decision-making (SDM) are well documented in the literature. The purpose of this study was to design an SDM model for diabetic patients. Materials and Methods: This qualitative content analysis study was performed in three steps. First, a descriptive comparative study was conducted using the widely-used George Brady method. Next, the perceptions of participants (both physicians and patients) were collected via interview and in focus group discussions (FGDs). Content analysis was used to categorize the comments made by participants. In the final step, the model of SDM for diabetic patients was designed based on expert panel discussions. Results: Twelve components were extracted from the comparative study. Two themes and six sub-themes were extracted from data resulting from physicians’ interviews, and two themes and ten sub-themes were extracted from data resulting from the FGDs involving patients. The model of SDM for diabetic patients was designed in light of three concepts; practitioners’ behavior, participatory decision-making process, and patients’ autonomy. Conclusion: This model was valuable because it recognizes the process of SDM in the context of Iran. The model’s main purpose was to help choose optimum strategies for the care of diabetic patients within the health sector. [GMJ.2021;10:e1735]